CNC Milling Machine's Structure's and Parts' Effect on Ability to Produce Dimensionally Accurate Parts Out of Metal - Hellström, Sasu (My University, 2025)
In this thesis factors of a CNC machine system that could affect CNC milling machine positioning accuracy during machining are considered. Different approaches to solving basic design challenges in machine frames are raised. A focus of this thesis was a thorough mapping of various parameters, phenomenon and behaviour of a CNC machine frame structure. Static and dynamic stiffness of the various structural elements of a CNC milling machine structure are considered based on their effects on the resulting machining accuracy. In this thesis methods of achieving lightweight but stiff and well-damping structures are also considered. Good design practices of a machine frame should be utilized when designing a CNC milling machine. The usage of FEM-simulations is relevant.
Keywords: milling machine structure, structural rigidity, resonance damping, milling accuracy